Validation of the combination Iranecio jurineifolius (Asteraceae, Senecioneae) from Turkey - Negaresh, Kazem (Phytotaxa, 2020)
The previously invalidly published combination Iranecio jurineifolius (Boiss. & Balansa) C.Jeffrey is here validated by citing the complete and correct details for the basionym. This species is morphologically similar to I. hypochionaeus and I. eriospermus, but differs from both by its scapiform stem, much reduced cauline leaves, solitary capitula and a greater number of calycular bracts. In addition, the current lectotypification of the species name is rejected.